Mental health of displaced and refugee children resettled in high-income countries: risk and protective factors. - Fazel, M; Reed, R; Panter-Brick, C; Stein, A (2012)
We undertook a systematic search and review of individual, family, community, and societal risk and protective factors for mental health in children and adolescents who are forcibly displaced to high-income countries. Exposure to violence has been shown to be a key risk factor, whereas stable settlement and social support in the host country have a positive effect on the child's psychological functioning. Further research is needed to identify the relevant processes, contexts, and interplay between the many predictor variables hitherto identified as affecting mental health vulnerability and resilience. Research designs are needed that enable longitudinal investigation of individual, community, and societal contexts, rather than designs restricted to investigation of the associations between adverse exposures and psychological symptoms. We emphasise the need to develop comprehensive policies to ensure a rapid resolution of asylum claims and the effective integration of internally displaced and refugee children.